Le pied de Sérapis de la sculpture à l’intaille : étude d’un thème isiaque caractéristique - Barcat, Dominique (Acta Classica Universitatis Scientiarum Debreceniensis, 2021)
The so-called foot of Serapis sculptures (i.e. those in the round with a bust of Serapis directly on top of a right foot) are well known and studied. Nevertheless, it was still necessary to take into account the representations of this motif in other media, such as gems and coins. And that is precisely the purpose of the present paper. In the following pages, these images are analyzed in the iconographical context of their period (1st and 2nd centuries CE). Such an approach allows us to observe the development of the motif in the different materials. In addition, this analysis will help us better understand the meaning of this image, and also to formulate some theories concerning the possible uses of these gems.